2022
DOI: 10.3390/ijerph192315653
|View full text |Cite
|
Sign up to set email alerts
|

Digital Health Care, Telemedicine, and Medicolegal Issues in Orthopedics: A Review

Abstract: The use of technologies in medicine has great potential to reduce the costs of health care services by making appropriate decisions that provide timely patient care. The evolution of telemedicine poses a series of clinical and medicolegal considerations. However, only a few articles have dealt with telemedicine and orthopedics. This review assesses the ethical and medicolegal issues related to tele-orthopedics. A systematic review was performed including papers published between 2017 and 2021 focusing on the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Hence, we should prioritize addressing medical errors by combining the age and affected sites of patients in clinical practice. Additionally, the COVID-19 pandemic has given to the spread of telemedicine in the orthopaedic field ( 37 ), which might be an effective approach to improve the patient safety in the orthopaedic specialty. Previous interventions might be less effective, as they are slightly generic and exceedingly concentrated on the operation stage.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, we should prioritize addressing medical errors by combining the age and affected sites of patients in clinical practice. Additionally, the COVID-19 pandemic has given to the spread of telemedicine in the orthopaedic field ( 37 ), which might be an effective approach to improve the patient safety in the orthopaedic specialty. Previous interventions might be less effective, as they are slightly generic and exceedingly concentrated on the operation stage.…”
Section: Discussionmentioning
confidence: 99%
“…The pandemic has also triggered efforts to increase health literacy, which positively influences the willingness to share PHI ( 40 ). Owing to the spread of COVID-19, many health providers adopted telemedicine, which allowed the delivery of health care services without any close contact ( 41 , 42 ). Whether and how telemedicine may have provided a vast amount of digital PHI and influenced the likelihood of sharing PHI remain unclear and deserve a deeper analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Other recent studies have shown that in-person clinical examination is necessary to confirm suspected instability of the shoulder [39][40][41][42][43][44].…”
Section: Discussionmentioning
confidence: 99%